2002
DOI: 10.1081/css-120014463
|View full text |Cite
|
Sign up to set email alerts
|

Rationale of the Economy of Soil Testing

Abstract: Probably the cheapest and most widely used chemical analysis employed in agriculture, soil testing is often not properly appreciated for the advantages it has for economically sound fertilizer recommendation for crops. In fact, soil testing is not only useful, but it becomes indispensable for this purpose, considering that it is used to determine unfavorable soil reaction and nutrient deficiencies and excesses that affect plant growth. To demonstrate how soil analysis and the economy of fertilizer use are inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 14 publications
0
12
0
4
Order By: Relevance
“…Two field experiments were conducted in the 2019-2020 season in Brazil with runner-type peanut cultivar Granoleico (InfoLEG, 2003) in Brazil. Sites were in adjacent fields near Regente Feijó in São Paulo State at 22˚13′9″ S, 51˚18′25″ W, 483 m elevation with sandy Arenic Hapludults soil of low fertility and much iron and aluminum oxides (Table 1) (Raij et al, 2001). One experiment in Brazil was on a site of terminated perennial degraded pasture of predominantly Urochloa [Urochloa decumbens (Stapf) R. Webster] (peanut following pasture).…”
Section: Characterization Of the Experimental Fieldsmentioning
confidence: 99%
“…Two field experiments were conducted in the 2019-2020 season in Brazil with runner-type peanut cultivar Granoleico (InfoLEG, 2003) in Brazil. Sites were in adjacent fields near Regente Feijó in São Paulo State at 22˚13′9″ S, 51˚18′25″ W, 483 m elevation with sandy Arenic Hapludults soil of low fertility and much iron and aluminum oxides (Table 1) (Raij et al, 2001). One experiment in Brazil was on a site of terminated perennial degraded pasture of predominantly Urochloa [Urochloa decumbens (Stapf) R. Webster] (peanut following pasture).…”
Section: Characterization Of the Experimental Fieldsmentioning
confidence: 99%
“…Phosphorus is one of the most expensive and widely used major nutrients used in broadacre cropping in Australia (FIFA 2008) and globally (van Raij et al 2002). Therefore, there is a major economic benefit in developing a soil test capable of accurately predicting the P status of a soil, which in turn will facilitate efficient fertilisation strategies and reduce the risks of environmental pollution due to over fertilising.…”
Section: Introductionmentioning
confidence: 99%
“…Soil correction and fertilization management followed the recommendations for sugarcane cultivation in Brazil (van Raij et al, 1997). The chemical characteristics of the soil were determined at depths of 0.00-0.25 and 0.25-0.50 m (van Raij et al, 2001), and the results and soil classification are shown in Table 1 (Soil Survey Staff, 2014).…”
Section: Site Descriptionmentioning
confidence: 99%